Jackfruit (Artocarpus heterophyllus) and breadfruit (A. altilis): phytochemistry, pharmacology, commercial uses and perspectives for human nourishment - Raihandhany, Reza (2020)
The Artocarpus J. R. & G. Forster genus is comprised of about 50 species. Artocarpus is derived from the Greek word artos, meaning bread while karpos means fruit. There are two species that are widely distributed in tropical regions, Artocarpus heterophyllus Lam., known as jackfruit, and Artocarpus altilis (Parkinson) Fosberg, known as breadfruit, both in the Moraceae or mulberry family. Both of these Artocarpus species have medicinal properties and biological activities that are derived from almost every part of the tree, fruit, seed, wood, bark, leaves and sap. This review examines the limited work that has been conducted on the biology and biotechnology of these two Artocarpus species with the hope that this knowledge may spur further basic and applied research.